2010
DOI: 10.1007/s11250-010-9708-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of extra-intestinal porcine helminth infections and assessment of sanitary conditions of pig slaughter slabs in Dar es Salaam city, Tanzania

Abstract: A study was carried out to establish the prevalence of extra-intestinal porcine helminth infections and to assess the pig slaughter slab sanitary conditions in Dar es Salaam city, Tanzania. A total of 24 privately owned pig slaughter slabs were assessed. All slaughter slabs were sub-standard; wrongly located, poorly designed and constructed and lacked most basic requirements for a slaughter house. Because of inadequate slaughtering, disposal and cleaning facilities, the slaughter slabs were under unhygienic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…Up to 4.03% of slaughtered pig had their liver condemned due to liver ascariasis. Studies by Ngowi et al (2004) and Mkupasi et al (2010) reported higher prevalence rates of liver ascariasis than the current study in other regions in Tanzania. Such difference in prevalence may again be contributed by limitations of abattoir records, pig management systems and diagnosis methods used.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Up to 4.03% of slaughtered pig had their liver condemned due to liver ascariasis. Studies by Ngowi et al (2004) and Mkupasi et al (2010) reported higher prevalence rates of liver ascariasis than the current study in other regions in Tanzania. Such difference in prevalence may again be contributed by limitations of abattoir records, pig management systems and diagnosis methods used.…”
Section: Discussioncontrasting
confidence: 82%
“…This rate is lower than 5.9% reported in Dar es Salaam slaughter slabs (Mkupasi et al 2010). Abattoir survey carried out in 1995 in northern Tanzania showed a prevalence ranging from 4.5% to 37.7% (Boa et al 1995).…”
Section: Discussionmentioning
confidence: 59%
“…Transportation of pigs and pork from rural cysticercosis endemic areas increases the risk of transporting infected and diseased pigs/pork into non-endemic urban areas for slaughter/sell as evidenced by [13] who found 5.9% of pigs brought into Dar es Salaam for slaughter were infected with T. solium by routine meat inspection. This has important epidemiologic implications for the country regarding transmission of cysticercosis/taeniosis especially in urban areas where pig keeping is not practiced but pork consumed.…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania T. solium is considered widespread in the northern, central, and southern regions based on porcine cysticercosis surveys [9], [10], [11], [12], [13]. These surveys provide initial evidence that T. solium infection is of national importance.…”
Section: Introductionmentioning
confidence: 99%
“…The free range system of keeping pigs, lack and or improper use of latrines, clandestine slaughtering and marketing of pork, absence of pork inspection and barbecuing [21][22][23], further increase the risk of human cysticercosis infection in Tanzania populations'. With the reported high risks of human cysticercosis, studies mainly have been reporting porcine cysticercosis [1,6,21,24]. The few studies that report cysticercosis infections in human are based on neuro cysticercosis particularly to people with epilepsy [2,25].…”
Section: Introductionmentioning
confidence: 99%